Root anatomy of Galeandra leptoceras (Orchidaceae) - Barretta-dos-Santos, Leila E.; Sant’Ana, Jéssica; Petini-Benelli, Adarilda; Pedroso-de-Moraes, Cristiano (Lankesteriana: International Journal on Orchidology, 2015)
Due to the scarce information about the root organization of Galeandra genus representatives, this study aimed to describe the root anatomy of Galeandra leptoceras, describing adaptations related to hydric relations and characters of taxonomic interest. Five roots of three plants were fixed and preserved in 50% alcohol. These ones were cut in midline with the use of razors. The sections were stained with 0.05% Safrablau and mounted in glycerin. It was observed that the roots of species are structurally adapted to epiphytism; however, some anatomical features show that this species requires more frequent watering or environments with constant humidity. The anatomical characteristics described for roots support results reported by authors that include the genus in subtribe Catasetinae, Cymbidieae tribe. The anatomical characters have generic uniformity, serving as a tool for the genus’s systematic.